Skin Lipids and Their Influence on Skin Microbiome and Skin Care - Siqueira, Raquel Allen Garcia Barbeto; Hradkova, Iveta; Leite-Silva, Vânia Rodrigues; Andréo-Filho, Newton; Lopes, Patricia Santos (ACS omega, 2025)
Skin lipids are essential components that play crucial roles in maintaining the skin barrier, preventing transepidermal water loss, and protecting against external agents. The specific composition of lipids may vary according to factors, such as age, diet, and environmental conditions. They are found predominantly in the stratum corneum, the outermost layer of the epidermis, with lipids originating from epidermal lipids and also from the sebaceous glands. The diversity of lipids, including ceramides, cholesterol, free fatty acids, sphingolipids, phospholipids, triglycerides, and waxes, reflects the complexity of their functions. Understanding the properties and biosynthesis of skin lipids is fundamental for advancing dermatology, developing treatments for various skin conditions, and maintaining the integrity of the skin barrier. Skin microbiome could affect skin lipid composition, and this topic has yet to be completely understood. This literature review aims to understand the properties of lipids found in the skin, the function and importance of fatty acids for skin maintenance and integrity, and their correlations that influence homeostasis: pH, the role of lipids in the microbiota, and finally, daily care practices that can influence the health of the skin and also the microbiome.